Clinical and economic results of laparoscopic versus open surgery in the treatment of hepatic hydatid cyst - Cornejo-Carrasco, Consuelo Elsa (2020)
Introduction: Our country has a high prevalence rate of hydatid cyst. The present study, was performed ina national reference center, and it is the first Peruvian study to compare the clinical and economic resultsof surgical techniques for the treatment of this disease. Objective: To compare the clinical and economicresults for laparoscopic surgery and open surgery in the treatment of hepatic hydatid cyst. Methods: Themedical records of all patients who underwent open partial cystectomy and laparoscopic partial cystectomy(2013-2015) were retrospectively reviewed. Morbidity, mortality, recurrence, operative time, length ofhospital stay, postoperative pain, and medical rest were evaluated. The costs per patient were found usingthe ABC costing system. Results: 22 patients were underwent open partial cystectomy (group 1) and 13underwent laparoscopic (group 2). There weren ́t differences in operative time, surgical complications, withpostoperative morbidity of 27.3% (group 1) and 30.7% (group 2). The conversion rate was 18.7%. There weren ́tcases of in hospital-mortality and one case of recurrence (4.5%) post open surgery. There weren ́t differencesbetween operative, postoperative and overall cost. Although the overall cost was lower for laparoscopicsurgery (1 700.99 ± 1 195.82 USD for group 1 and 1 561.83 ± 702.53 USD for group 2) but without significantdifferences (p = 0.64). There was less postoperative pain, shorter hospital stay and duration of medical rest (p<0.05). Conclusion: The clinical and economic results were similar for both types of surgery; However, therewas less post-operative pain, hospital stay, and quicker reintegration into working life for patients operatedby laparoscopic surgery.Key words: Echinococcosis